Concise syntheses and HCV NS5B polymerase inhibition of (2′R)-3 and (2′S)-2′-ethynyluridine-10 and related nucleosides. Issue 23 (1st December 2017) - Bennett, Frank; Buevich, Alexei V.; Huang, Hsueh-Cheng; Girijavallabhan, Vinay; Kerekes, Angela D.; Huang, Yuhua; Malikzay, Asra; Smith, Elizabeth; Ferrari, Eric; Senior, Mary; Osterman, Rebecca; Wang, Lingyan; et al.
Graphical abstract: Abstract: (2′ R )-Ethynyl uridine3, and its (2′ S )-diastereomer10, are synthesised in a divergent fashion from the inexpensive parent nucleoside. Both nucleoside analogues are obtained from a total of 5 simple synthetic steps and 3 trivial column chromatography purifications. To evaluate their effectiveness against HCV NS5B polymerase, the nucleosides were converted to their respective 5′-O-triphosphates. Subsequently, this lead to the discovery of the 2′-β-ethynyl18 and -propynyl20 nucleotides having significantly improved potency over Sofosbuvir triphosphate24 .